Pembatasan dan Kontrol Pers pada Novel Jejak Langkah Karya Pramoedya Ananta Toer - Alda Mustika Rani; Aliasan .; Jufrizal . (CV. ITTC INDONESIA, 2026)
This study, entitled Press Restriction and Control in the Novel Jejak Langkah by Pramoedya Ananta Toer, examines the dynamics of colonial power over the indigenous press as represented in the third volume of the Buru Quartet. The novel portrays the socio-political conditions of the Dutch East Indies during the early phase of the national awakening through the experiences of Minke, an educated native who engages in journalism as a form of resistance against colonial injustice. This research is guided by two main problem formulations: how the Dutch colonial government imposed forms of restriction and control over press activities carried out by Minke in the novel Jejak Langkah, and how such restrictions and controls affected Minke’s movement and ideological development. This study employs a qualitative approach using literary text analysis, with data obtained from primary sources (the novel Jejak Langkah) and secondary sources such as books, journals, and relevant scholarly works. The analysis is framed using the theory of disciplinary power proposed by Michel Foucault. The findings reveal that colonial authorities exercised control over the press through censorship, strict press regulations, legal sanctions, economic pressure, and exile. These mechanisms functioned as instruments to suppress critical discourse and maintain colonial dominance. Furthermore, these restrictions significantly influenced Minke’s transformation from an individual-oriented thinker into a figure with collective awareness, emphasizing organized resistance and public advocacy. In conclusion, the novel Jejak Langkah reflects not only the historical reality of colonial press suppression but also the enduring tension between media and power. The struggle experienced by Minke demonstrates that press freedom is the result of continuous resistance against control, making the novel relevant to contemporary discussions on media independence.